(untitled) (International Journal of Engineering and Computer Science, 2024)
This paper proposes a novel Lambda Authorizer Benchmarking Tool utilizing AWS Serverless Application Model (SAM) and Artillery framework. The tool evaluates the performance of serverless functions implementing Lambda Authorizers. We focus on three key performance parameters: cold start behaviour, programming language runtimes, and authorization types (e.g., token-based, claim-based). By employing load testing with Artillery, the tool measures the impact of these factors on authorization processing speed and resource consumption. The findings from the benchmarking experiments offer valuable insights for developers building secure and cost-effective serverless APIs with Lambda Authorizers. The tool empowers and developers to make informed decisions regarding programming language selection, authorization strategy, and optimization techniques for their serverless applications.